Comparison of Effectiveness of Interactive and Non-interactive Virtual Education about Brain Death and Organ Transplantation on Knowledge and Satisfaction of Critical Care Nurses - Seyed Ali Mahdiyoun; Masoomeh Imanipour; Rita Mojtahedzadeh; Agha Fatemeh Hosseini (Tehran University of Medical Sciences, 2015)
Background & Aim: Virtual education can be delivered via different routes. The purpose of this study was to investigate the effectiveness of interactive and non-interactive virtual educations about brain death and organ transplantation on knowledge and satisfaction of education among intensive care nurses .   Methods & Materials: This quasi-experimental study was conducted on intensive care nurses of hospitals affiliated to Tehran University of Medical Sciences in 2014 . Participants were selected through a convenient sampling method and were assigned into two groups with 32 participants in each. The first group participated in an interactive electronic education; while the second group received a non-interactive education about brain death and organ transplantation . Knowledge of both groups was measured before and after the education. The satisfaction of participants with the course was measured using a questionnaire. The scores were compared within and between groups using the paired and independent t-test, respectively .    Results: The knowledge of both groups increased significantly after the intervention (P<0.001); however, there was no significant difference between the mean scores of the two groups after the education (P<0.05). The s atisfaction with the course was significantly higher in the interactive education group (P=0.04) .   Conclusion: B oth interactive and non-interactive electronic educations increased the knowledge of nurses. The nurses were more satisfied with the interactive education. Further studies are recommended .